2019
DOI: 10.1016/j.heliyon.2019.e02146
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of transesterification using particle swarm optimization method

Abstract: In the present work, an optimization method called Particle Swarm Optimization (PSO) was applied to study the kinetics of alkali-catalyzed rapeseed oil transesterification, using methanol, in a batch process. The validation of the PSO program was realized using numerical and experimental data from literature. The PSO method resulted in a 4 times lower error compared to classic methods used in the domain, which showed its efficiency and strength. After validation, an experimental study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…[129][130][131] For the specific case of kinetic models, the EAs have been employed to estimate values for the unknown kinetic rate constants, in particular, when it is a large number of unknown constants. [26,[132][133][134] This approach has been successfully employed for a variety of reactions and reactive systems. Therefore, the application of EAs could provide interesting advances on the study of AOPs.…”
Section: Evolutionary Optimization Algorithmsmentioning
confidence: 99%
“…[129][130][131] For the specific case of kinetic models, the EAs have been employed to estimate values for the unknown kinetic rate constants, in particular, when it is a large number of unknown constants. [26,[132][133][134] This approach has been successfully employed for a variety of reactions and reactive systems. Therefore, the application of EAs could provide interesting advances on the study of AOPs.…”
Section: Evolutionary Optimization Algorithmsmentioning
confidence: 99%
“…Previous kinetic studies proposed that oil and alcohol type, alcohol-to-oil molar ratio, catalyst type and concentration, and reactor stirring speed were parameters to take into consideration [12][13][14][15][16][17][18][19][20]. Then, performing the reaction at different temperatures provided information to further calculate activation energy and, thus, rate constants.…”
Section: Analysis Of Process Variablesmentioning
confidence: 99%
“…Esterification using H 2 SO 4 as a catalyst has been carried out with methanol and either coconut or sunflower oil, and with ethanol and sunflower oil, at different temperatures and concentrations [12,13]. In the same way, methanolysis has been carried out using KOH or NaOH as catalyst, using rapeseed oil [14], sunflower oil [15,16], Pongamia pinnata oil [17], Brassica carinata oil [18], palm oil [19] or soybean oil [20,21] also at different temperatures and concentrations. However, only a few kinetic studies about enzyme-or lipase-assisted transesterification have been reported [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, Kadi et al formulated a mathematical model to evaluate rapeseed oil transesterification. In their study, a PSO algorithm was employed [41]. Additionally, Ding et al assessed both PSO and GA to model biomass pyrolysis based on 14 rate constants [42].…”
Section: Introductionmentioning
confidence: 99%